PARACETAMOL DISPENSING PRACTICE OF GOVERNMENT HEALTH CLINICS POST INFANTS’ VACCINATION IN MALAYSIA - SULEIMAN, NURAIN; SHAMSUDIN, SITI HADIJAH; RUS, RAZMAN MOHD; DRAMAN, SAMSUL (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: This study obtained information on Paracetamol (PCM) Dispensing Practice of Government Health Clinics (GHC) post infants’ vaccination in Malaysia as well as identify its possible factors. Methods: This descriptive cross-sectional retrospective study (with convenient sampling) using a data collection form (DCF) to collect data. The pharmacist who is the representative of the GHC filled the DCF. Potential risk factors were evaluated by Pearson chi-square tests (expected count<5 is<20%) for an independent sample. Results: A total number of 254 samples were collected all over Malaysia within the period of data collection, but only 248 that met inclusion criteria. The PCM dispensing practice of GHC in Malaysia for a total period of 3 y back (from 2015-2017), tend not to give PCM post immunization with respect to age of the upon vaccination and types of vaccination, conversely for gender. Trends of PCM dispensing practice were increasing for “Not Give PCM” with respect to gender, age of the baby upon vaccination, and types of vaccination from 2015 till 2017. The PCM dispensing practice had no association with no statistically significant value (p=0.804) on genders and a weak positive association with statistically significant value (p<0.05 each) on age of the baby (≤ 1year) upon vaccination and types of vaccination. Conclusion: Future research which may include the actual practice in which practices of prescribers or mother may be conducted in determining more accurate data on the giving PCM post infant’s vaccination.